Clinical and radiological results of patients treated with two loading protocols for mandibular overdentures on Bra°nemark implants - Ilser Turkyilmaz (journal of clinical periodontology, 2006)
Objective: The aim of this study was to evaluate clinical and radiological outcomes of the unsplinted implants supporting mandibular overdenture when applying conventional or early loading protocols. Material and Methods: Twenty-six edentulous patients were treated with two unsplinted Bra°nemark System implants supporting mandibular overdenture. There was a test group, in which the overdenture was connected 1 week after surgery, and a control group, in which the overdenture was connected 3 months after surgery. Periimplant paremeters were recorded 1, 6, and 12 months after surgery. Clinical stability measurements were performed at surgery, and after 3, 6, and 12 months. Marginal bone levels were evaluated at implant surgery, after 6, and after 12 months. Results: No implant from either group was lost. Clinical peri-implant parameters, clinical stability measurements, and marginal bone resorptions showed no statistically significant differences between two groups during 12 months. Conclusion: The results of this study suggest that one-week of early loading protocol of two Bra°nemark implants supporting mandibular overdenture does not compromise implant stability, marginal bone loss, and peri-implant soft-tissue health.